Controlled One-pot Synthesis of Nickel Single Atoms Embedded in Carbon Nanotube and Graphene Supports with High Loading - Zhao, Shiyong; Wang, T.; Zhou, G.; Zhang, L.; Lin, C.; Veder, Jean-Pierre; Johannessen, B.; Saunders, M.; Yin, L.; Liu, C.; De Marco, Roland; Yang, S.Z.; et al. (WILEY-V C H VERLAG GMBH, 2020)
Single-atom catalysts (SACs) have attracted much attentions due to the advantages of high catalysis efficiency and selectivity. However, the controllable and efficient synthesis of SACs remains a significant challenge. Herein, we report a controlled one-pot synthesis of nickel single atoms embedded on nitrogen-doped carbon nanotubes (NiSA−N−CNT) and nitrogen-doped graphene (NiSA−N−G). The formation of NiSA−N−CNT is due to the solid-to-solid rolling up mechanism during the high temperature pyrolysis at 800 °C from the stacked and layered Ni-doped g-C3N4, g-C3N4−Ni structure to a tubular CNT structure. Addition of citric acid introduces an amorphous carbon source on the layered g-C3N4−Ni and after annealing at the same temperature of 800 °C, instead of formation of NiSA−N−CNT, Ni single atoms embedded in planar graphene type supports, NiSA−N−G were obtained. The density functional theory (DFT) calculation indicates the introduction of amorphous carbon source substantially reduces the structure fluctuation or curvature of layered g-C3N4-Ni intermediate products, thus interrupting the solid-to-solid rolling process and leading to the formation of planar graphene type supports for Ni single atoms. The as-synthesized NiSA−N−G with Ni atomic loading of ∼6 wt% catalysts shows a better activity and stability for the CO2 reduction reaction (CO2RR) than NiSA−N−CNT with Ni atomic loading of ∼15 wt% due to the open and exposed Ni single atom active sites in NiSA−N−G. This study demonstrates for the first time the feasibility in the control of the microstructure of carbon supports in the synthesis of SACs.